Do Indonesian Laws and Policies on Covid-19 Countermeasures Action Reflect Legality? - I Made Arya Utama (Faculty of law Udayana University, 2020)
Every citizen has the right to access the resources and health facilities, social security, health services, as well as attaining the highest degree of health. At the present, Covid-19 has become a global pandemic and has been declared a non-natural disaster, which could potentially be related to the citizen’s right to health as regulated with statutory law. This article analyses the dynamics that reflect the legality of national statutory law in the response Covid-19 in Indonesia. This article is based on normative legal research using a statutory approach and conceptual approach. The study found that the right to health has properly been regulated in the Constitution as well as human rights and health-related legislations, reflecting the presence of the state to interfere with the health problems of its citizens. Besides, this study suggests that legal culture, as a component of legal system theory, remains an issue in the efforts of handling the pandemic. There is still a part of the society that is not able to readily and consciously participate and involve in the response to Covid-19 in Indonesia.